Metabolic accompaniments of variants of uric acid exchange - Bombushkar, Igor (Journal of Education, Health and Sport, 2022)
Background. During the implementation of the project "Physiological activity of uric acid", our group discovered four variants of the combination of levels of uricemia and uricosuria in patients with chronic pyelonephritis in the remission phase, which are accompanied by characteristic constellations of parameters of the autonomic nervous, endocrine, and immune systems, the levels of which correlate with uricemia and/or uricosuria. The aim of this study is to clarify the relationship between parameters of exchange of uric acid and other metabolites. Materials and methods. Under an observations were 34 males (23-70 years) and 10 females (33-76 years) with chronic pyelonephritis in the phase of remission. The object of the study was serum and urine levels of uric acid as well as calcium, magnesium, phosphates, chloride, sodium, potassium, creatinine, urea and glucose. Results. Among all registered parameters, 12 were identified as characteristic of the four variants of uric acid metabolism. The discriminant model includes, in addition to uricosuria and uricemia by definition, blood levels of creatinine, urea, glucose, phosphates, magnesium, and potassium, creatinineuria as well as body mass index, electrokinetic index and sex index. According to the results of the canonical correlation analysis, it was established that balneotherapy-induced concomitant changes in uricosuria and uricemia positively determine changes in diuresis and excretion of urea, magnesium, sodium, phosphates, calcium, potassium and chloride, as well as calciumemia and magnesiumemia. Conclusion. The uric acid molecule, as a structural analog of methylxanthines and adenosine, exerts the metabolic effects, probably, as the consequences of its neuro-endocrine effects.